How Safe Are You? Themes, Concerns and Metaphor of Jewish Second-Generation Literature in the Novel "To Life" - Warner, Kirsten (Auckland University of Technology, 2012)
The novel To Life concerns the inheritance of psychic trauma by the child of a survivor of the Jewish Holocaust, and is part of the genre of second-generation literature. In this exegesis I will examine the genre’s frames of reference and some of its themes and concerns as relating to the novel To Life. Firstly, I will discuss some of the creative process of writing the novel, and why I felt compelled to do so. Within that I discuss feelings of lack of entitlement as a second-generation writer, and the transformation of personal history into fiction. I then examine ‘second generation’ as a psychological description of growing up with the Holocaust, and how I have tried to recreate this in the novel. I will outline the frames of reference of second-generation literature and how they shaped this novel. In particular I will examine voice, tense and point of view; memory and postmemory; and the subconscious made conscious. The exegesis identifies metaphor as a tool for second-generation writers. In related works and in To Life, I discuss how megametaphor operates through the text as a whole, by representation, comparison and association, to indicate that something is going on under the surface. In To Life, the underlying question for someone of the second generation is, “How safe are you?”
Keywords: Second-generation; 2G; Holocaust; Jewish; Post-memory; Survivor